Essentials of world regional geography - Bradshaw, Michael J. |q(Michael John) 1935- (Boston McGraw-Hill higher education, 2008)
Essentials of world regional geography; Europe; Russia and neighboring countries; East Asia; Southeast Asia, Australia, and Oceania; South Asia; Northern Africa and Southwestern Asia; Africa South of the Sahara; Latin America; North America.
Includes index
Keywords: Geography -- Textbooks; Địa lý